IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT BERWIRAUSAHA MAHASISWA - Primandha Sukma Nur Wardhani; Dian Nastiti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
One of the factors for the growth of entrepreneurship in a country lies in the role of higher education institutions through the provision of entrepreneurship education. Entrepreneurship education not only provides a theoretical basis for the concept of entrepreneurship, but can also shape the mindset, behavior and views of students about entrepreneurship. This study aims to determine the concept of entrepreneurship education, the implementation of entrepreneurship education in lectures to foster interest in entrepreneurship among students, factors that can foster student entrepreneurship interest, and the benefits of entrepreneurship lectures for students. This research is a type of qualitative research with a phenomenological approach. Subject determination by purposive sampling. Data collection techniques with observation, documentation, interviews. Data validation technique is triagulation technique. The results of the research on the concept of entrepreneurship education that are applied from entrepreneurship education to students are entrepreneurship education integrated into entrepreneurship courses. (2) Implementation of entrepreneurship education in lectures to foster interest in entrepreneurship in students integrating it in the form of teaching in the form of material and practice (3) Factors that can foster interest in entrepreneurship consist of internal and external factors as well as supporting and inhibiting factors (4) the benefits of entrepreneurship lectures in fostering interest in entrepreneurship has a good impact on students by providing entrepreneurial skills, adding entrepreneurial insight, forming motivation, and mentally training when doing business.